Analisis Metode Pembelajaran “Riddle Games Economics” Sebagai Alat Evaluasi Pembelajaran Pada Pokok Bahasan Perdagangan Internasional - Dhita Aulia Rahmayanti; Early Ni'mah Hayati (Jurnal Pendidikan Ekonomi, 2023)
The learning activities of an educator must perform an assessment or evaluation after the material submitted has been completed. Evaluation aims to measure the students' mastery and understanding of the subject or subject. It can be an educational game that has been adapted to the needs of learning in a class called a game based learning or educational game where the game also serves as an evaluator of students learning outcomes. This study aims to identify the application of economic learning innovation based on educational games. This type of research is a qualitative study by conducting a descriptive analysis of an educational game application of Riddle Games Economics as a form of learning innovation in terms of learning methods to learn about a topic that is applied to teaching Assistance Economics at SMAN 1 Lawang.